Childhood‐Onset Choreo‐Dystonia Due to a Recurrent Novel Homozygous Nonsense HPCA Variant: Case Series and Literature Review. Issue 1 (23rd August 2022) - Magrinelli, Francesca; Bhatia, Kailash P.; Beiraghi Toosi, Mehran; Arab, Fatemeh; Karimiani, Ehsan Ghayoor; Sedighzadeh, Sahar; Ansari, Behnaz; Neshatdoust, Maedeh; Rocca, Clarissa; Houlden, Henry; Maroofian, Reza
Abstract: Background: Biallelic variants in HPCA were linked to isolated dystonia (formerly DYT2) in 2015. Since then, the clinical spectrum of HPCA ‐related disorder has expanded up to including a complex syndrome encompassing neurodevelopmental delay, generalized dystonia with bulbar involvement, and infantile seizures. Cases: We report four individuals with a new phenotype of childhood‐onset choreo‐dystonia belonging to two unrelated Iranian pedigrees and harboring a novel homozygous nonsense pathogenic variant NM_002143.3:c.49C>T p.(Arg17*) in HPCA . Although the families are both Iranian, haplotype analysis of the exome data did not reveal a founder effect of the variant. Literature Review: A systematic review of articles on HPCA and dystonia published since the disease gene discovery (PubMed; search on July 09, 2022; search strategy "HPCA AND dystonia", "HPCA AND movement disorder", "hippocalcin AND dystonia", and "hippocalcin AND movement disorder"; no language restriction) resulted in 18 references reporting 10 cases from six families. HPCA ‐related dystonia was isolated or in various combinations with neurodevelopmental delay, intellectual disability, seizures, cognitive decline, and psychiatric comorbidity. Onset of dystonia ranged from infancy to early adulthood. Dystonia started in the limbs or neck and became generalized in most cases. Brain MRI was unremarkable in nearly all cases where performed. There was poor or no response to common antidystonic medications in most cases. Conclusions: Our case series expands the pheno‐genotypic spectrum of HPCA ‐related disorder by describing childhood‐onset choreo‐dystonia as a new phenotype, reporting on a recurrent novel pathogenic nonsense variant in HPCA, and suggesting that exon 2 of HPCA might be a mutational hotspot.